Effect of Combined Action of Extracellular ATP and Elevated Calcium on Osteogenic Differentiation of Primary Cultures from Rat Calvaria - Laiuppa, Juan Andrés (2016)
The in vitro osteogenic differentiation has been intensively studied. However, it is not yet clear precisely how osteogenesis can be optimized.Changes in extracellular Ca2þ concentration ([Ca2þ]e), as well as modulation of purinergic receptors play an important role in the regulation ofosteoblasts differentiation and bone formation. In this study, we investigated the effects of a combined treatment of ATPg-S and high [Ca2þ]e(5.35 mM) on osteogenic differentiation and function of primary cell cultures from rat calvaria. Our results indicate that ATPg-S stimulates celltransition from the G0 to S phase of cell cycle, involving the PI3K signaling pathway. Treatment with 10 or 100 mM ATPg-S and [Ca2þ]e (ATP-[Ca2þ]e) for 48 h increases cell number significantly above the control. ATPg-S treatment in osteogenic medium containing [Ca2þ]e stimulatesthe gene expression of BMP-4, BMP-5, and OPN at 16, 48, and 72 h, respectively, above control. In same conditions, treatment for 6 days with10mMUTP or 100mMUDP significantly increased the ALP activity respect to control. Cells grown in osteogenic medium showed a statisticallysignificant increase in calcium deposits at 15 and 18 days, for 10mMATPg-S treatment, and at 18 and 22 days, for [Ca2þ]e treatment, respect tocontrol but ATP-[Ca2þ]e treatment shown a significant greater mineralization at 15 days respect to ATPg-S, and at 18 days respect to bothagonists. In conclusion, we demonstrated that an osteogenic medium containing 10mM ATPg-S and 5.35mM [Ca2þ]e enhance osteogenesisand mineralization by rat primary calvarial cells cultures.